Acute coronary syndromes and acute heart failure: a diagnostic dilemma and high‐risk combination. A statement from the Acute Heart Failure Committee of the Heart Failure Association of the European Society of Cardiology. (29th April 2020) - Harjola, Veli‐Pekka; Parissis, John; Bauersachs, Johann; Brunner‐La Rocca, Hans‐Peter; Bueno, Hector; Čelutkienė, Jelena; Chioncel, Ovidiu; Coats, Andrew J.S.; Collins, Sean P.; de Boer, Rudolf A.; Filippatos, Gerasimos; Gayat, Etienne; et al.
Abstract: Acute coronary syndrome is a precipitant of acute heart failure in a substantial proportion of cases, and the presence of both conditions is associated with a higher risk of short‐term mortality compared to acute coronary syndrome alone. The diagnosis of acute coronary syndrome in the setting of acute heart failure can be challenging. Patients may present with atypical or absent chest pain, electrocardiograms can be confounded by pre‐existing abnormalities, and cardiac biomarkers are frequently elevated in patients with chronic or acute heart failure, independently of acute coronary syndrome. It is important to distinguish transient or limited myocardial injury from primary myocardial infarction due to vascular events in patients presenting with acute heart failure. This paper outlines various clinical scenarios to help differentiate between these conditions and aims to provide clinicians with tools to aid in the recognition of acute coronary syndrome as a cause of acute heart failure. Interpretation of electrocardiogram and biomarker findings, and imaging techniques that may be helpful in the diagnostic work‐up are described. Guidelines recommend an immediate invasive strategy for patients with acute heart failure and acute coronary syndrome, regardless of electrocardiographic or biomarker findings. Pharmacological management of patients with acute coronary syndrome and acute heart failure should follow guidelines for each of these syndromes, with priority given to time‐sensitive therapies for both. Studies conducted specifically in patients with the combination of acute coronary syndrome and acute heart failure are needed to better define the management of these patients.